Consumo e ganho de peso de larvas de Chrysoperla Externa (Hagen, 1861) (Neuroptera: Chrysopidae) de diferentes Populaçoes e Geraçoes de Laboratório - De Bortoli, S.A.; Ferreira, R.J. (My University, 2008)
Several studies have been made about biology, predatory capacity, and food consumption to crisopids species, trying to get informations to use in Integrated Pest Management. Raising insects in laboratory for many generations could cause blood relation problems, even annihilate the insect mass production. In this way, the objective of this work was to determine the consumption and the weight gain to Chrysoperla externa larvae from two populations and different laboratory generations, founded by 1, 5, 10, 15 and 20 couples. By the result it was possible to conclude that larvae food consumption was higher in populations founded by greater number of couples, and it is not verified variation among populations and generations.
Food consumption and weight gain of Chrysoperla externa larvae from different laboratory populations and generations